(untitled) (Research, Society and Development, 2020)
Mastitis is a breast tissue disease with a high incidence in dairy cows and implications ranging from the health of the animals to the economy of the sector. Although antibiotic therapy is widely used, the search for new perspectives in the management and treatment of this disease is necessary. Although phage research preceded the discovery of antibiotics, with the appearance of antibiotics and their efficiency in treating infections, phage therapy fell into disuse. However, phage therapy has now re-emerged as an alternative for combating multidrug-resistant bacteria. The relationship between phages, bacteria, and the immune system is unique, generating a wide range of opportunities, some of which have yet to be studied. Thus, the objective of this review was to analyze the use of bacteriophages in the control of bovine mastitis and its association with other natural products today. Phages have been shown to exert effective antibacterial and anti-biofilm activity, and their interactions with other substances of natural origin could be a viable path for treating disease. Despite being little explored, phages are already being considered as an alternative for treatment against the main bacterial agents of mastitis. In this review, the safety and future pathways of phage therapy are addressed in order to indicate points where research still needs to progress and the main advantages and difficulties in this area.